SOSIALISASI PENTINGNYA KETERAMPILAN DAN PENGETAHUAN UNTUK MENINGKATKAN PELUANG KERJA DIDUNIA INDUSTRI PADA SMKN 1 KOTA SERANG - Anip, Anip Solihin; Ahmad Syarifudin Sukasih, S.M., M.M. (CV SWA Anugerah, 2025)
Socialization of the importance of skills and knowledge to increase job opportunities in the industrial world for SMK graduates, especially at SMKN 1 Kota Serang is an effort to increase understanding among SMK students that in order to join the industrial world today, prospective workers must really have the appropriate competencies so that they can be well accepted in the industrial world. Among the competencies that must be possessed are qualified skills and knowledge, especially if we look at graduates at the SMK (Vocational High School) level who have the motto